The impact of green entrepreneurial orientation, market orientation and green supply chain management practices on sustainable firm performance - Md. Ahashan Habib; Yukun Bao; Aboobucker Ilmudeen (Cogent Business & Management, 2020)
This study attempts to examine the impact of green entrepreneurial orientation (GEO) and market orientation (MO) on the implementation of green supply chain management (GSCM) practices and subsequent sustainable firm performance. Further, the study identifies the mediating factor between green entrepreneurial orientation and sustainable firm performance and also explores whether market orientation plays a mediating role in the relationship between GEO and GSCM practices. The data collected from 246 Bangladeshi textile manufacturing firms were analyzed using the structural equation modeling with partial least square techniques, typifying that exploratory and quantitative research. The results revealed that GEO has a significant positive influence on MO and GSCM practices, which ultimately positively effects on all the three dimensions (economic, environmental, and social) of sustainable firm performance. Further, the study found that GSCM practices partially mediate the relationship between GEO and firm performance while MO also partially mediate the relationship between GEO and GSCM practices. These findings indicate that organizations should emphasize on GSCM practices in their operations to reap sustainability performance. The theoretical and practical implications are also discussed.
Keywords: 650; green entrepreneurial orientation; green supply chain management; market orientation; sustainable performance; operation management; textile industry